Thinking about education from collaboration. Mitote as a collective work - Raggi Lucio, Adriana (2021)
This text aims to analyze how the relationship between education and community was addressed in the Mitotes of collaboration and exploration on artistic education from Simón Rodríguez, Juan Acha and Melquiades Herrera. We approached, through the report of an experience and the work with the archive of the event, to what happened in the meeting, which was formulated from educators such as Simón Rodríguez, Juan Acha, Melquiades Herrera and Lia García and our experiences in art and design education. The text reveals how the event rescued ideas of an education that starts from places far from domination and closer to dialogue between equals.